2020
DOI: 10.14309/ctg.0000000000000276
|View full text |Cite
|
Sign up to set email alerts
|

Human Milk Oligosaccharides Support Normal Bowel Function and Improve Symptoms of Irritable Bowel Syndrome: A Multicenter, Open-Label Trial

Abstract: INTRODUCTION: Treatment options for irritable bowel syndrome (IBS) are limited, causing many patients to remain symptomatic. This study assessed the potential of human milk oligosaccharides (HMOs) to normalize bowel habits. Secondary outcomes included IBS severity and health-related quality of life. METHODS: This multicenter, open-label trial recruited patients with IBS from 17 sites across the United States. Patients received daily orally administrated 5-g intervention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 40 publications
0
24
0
Order By: Relevance
“…Upon reaching the colon, HMOs serve as prebiotic agents by exerting bifidogenic effects, not only in breast-fed infants [ 17 , 18 ], but also in human adults [ 19 ]. Moreover, several clinical trials in IBS patients yielded positive results for the use of HMOs [ 20 , 21 ]. Besides the beneficial modulation of the gut microbiota, HMOs have also been shown to improve the gut barrier function [ 22 , 23 ], support immune development and modulate immune response [ 24 ], affect intestinal cell responses [ 25 ], and prevent the epithelial adhesion of intestinal pathogens [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Upon reaching the colon, HMOs serve as prebiotic agents by exerting bifidogenic effects, not only in breast-fed infants [ 17 , 18 ], but also in human adults [ 19 ]. Moreover, several clinical trials in IBS patients yielded positive results for the use of HMOs [ 20 , 21 ]. Besides the beneficial modulation of the gut microbiota, HMOs have also been shown to improve the gut barrier function [ 22 , 23 ], support immune development and modulate immune response [ 24 ], affect intestinal cell responses [ 25 ], and prevent the epithelial adhesion of intestinal pathogens [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, this study did not allow us to relate the changes seen in microbiota or metabolite profiles to the improvement of the patients, since the original clinical trial evaluated safety and was not aimed at assessing the improvement of IBS symptoms. Nevertheless, the intestinal microenvironment modulation described in this study, together with the improvement of IBS symptoms previously reported in an open label trial with 2 FL/LNnT [31], indicate that 2 FL/LNnT promote gut health by targeting bifidobacteria, and calls for further investigations in a larger cohort.…”
Section: Discussionmentioning
confidence: 49%
“…Although HMOs have been suggested as promising supplements for the management of patients with microbiota-gut-brain axis disorders [30], studies of HMOs in patients with IBS are still scarce. A large-scale open-label trial conducted in patients with IBS recently demonstrated that 2 FL/LNnT supplementation improved GI symptoms and quality of life [31]. In addition, our group recently reported in a placebo-controlled proof-of-concept study that a mix of 2 FL/LNnT is well tolerated and beneficially impacts fecal bifidobacteria abundance in IBS patients after a 4-week treatment period [32].…”
Section: Introductionmentioning
confidence: 97%
“…Recently, some commercially available synthesized HMOs, including 2′-FL, have been utilized in infant formula owing to their promising effects including prebiotic effects on Bifidobacterium sp. Several clinical trials have evaluated the safety, tolerance, and benefits of 2′-FL (and LNnT) in infants ( Reverri et al, 2018 ; Vandenplas et al, 2018 ; Berger et al, 2020 ) and adults ( Elison et al, 2016 ; Iribarren et al, 2020 ; Palsson et al, 2020 ), demonstrating modulation of the gut microbiota. Interestingly, 2′-FL and LNnT supplementation to infant formula increased the abundances of Bifidobacterium sp.…”
Section: Discussionmentioning
confidence: 99%